1980
DOI: 10.1128/jvi.33.1.366-376.1980
|View full text |Cite
|
Sign up to set email alerts
|

Role of the host cell in bacteriophage T4 development. I. Characterization of host mutants that block T4 head assembly

Abstract: To study the role of the host cell in bacteriophage T4 infection, we selected more than 600 mutant host-defective bacteria that absorbed and were killed by phage T4+ but were unable to support its growth. The mutants were grouped into seven classes by the growth patterns of T4 phages carrying compensating mutations (go mutants [grows on]), selected on four prototype host-defective strains. Lysis and DNA synthesis experiments indicated that classes A, AD, D, and B (the majority of the host-defective mutants) bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Out of 11 groEL mutants in our collection, only 1, mutant groEL44, does not allow T4 growth. In addition, we found that six out of six hd bacterial mutants of Revel et al (11), which block T4 head assembly at the level of gp3l action, map in the groEL gene (unpublished results). These findings suggest that gpgroES may be nonessential for T4 head assembly.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Out of 11 groEL mutants in our collection, only 1, mutant groEL44, does not allow T4 growth. In addition, we found that six out of six hd bacterial mutants of Revel et al (11), which block T4 head assembly at the level of gp3l action, map in the groEL gene (unpublished results). These findings suggest that gpgroES may be nonessential for T4 head assembly.…”
mentioning
confidence: 74%
“…We reasoned that if we could suppress mutations in one gene by mutating the second gene, this would support this hypothesis. The only groE mutants shown to block T4 growth (some of which permit A growth [11]) map in the groEL gene (unpublished data), so this distinguishing phenotype was used for selecting altered groEL genes. The strategy used for isolating specific intergenic suppressors was to start with groES mutants which are temperature sensitive for bacterial growth, isolate temperature-resistant derivatives, and screen those survivors for inability to propagate phage T4 or T4e1 (a T4 mutant able to grow on strain groEL44).…”
Section: Resultsmentioning
confidence: 99%
“…T5 infection of some groEL and groES mutants was abortive due to a block in an early stage of T5 tail assembly, a stage before recognizable structures were assembled or the proteolytic cleavage in the process was performed (281). In the case of T4, only groEL mutations were found to block head assembly, but the block occurs at an early stage of head assembly (26,79,203,245,246; K. Tilly and C. Georgopoulos, unpublished data). groE mutations confer a temperature-sensitive growth defect on the host (78).…”
Section: Dnamentioning
confidence: 98%
“…The process of T4+ capsid morphogenesis appears to involve the direct interaction of a host cell protein referred to as gpGroEL (21) with gp3l. This conclusion is based on the observation that T4 gene 31 mutants can overcome groEL host mutants in an allele specific manner (14). Furthermore, since specific T4 gene 23 mutants form plaques with high efficiencies on certain E. coli groEL mutants (14) and since gp3l appears to bind to lumps of capsid protein (5), it seems likely that gp23 also interacts directly with gpGroEL or with gp3l (or with both).…”
Section: Vol 51 1984mentioning
confidence: 99%
“…This conclusion is based on the observation that T4 gene 31 mutants can overcome groEL host mutants in an allele specific manner (14). Furthermore, since specific T4 gene 23 mutants form plaques with high efficiencies on certain E. coli groEL mutants (14) and since gp3l appears to bind to lumps of capsid protein (5), it seems likely that gp23 also interacts directly with gpGroEL or with gp3l (or with both). These observations and the conclusion, Autoradiograph of an SDS gel of purified T4 phage made in the presence and in the absence of gp31.…”
Section: Vol 51 1984mentioning
confidence: 99%